Maternagem e função materna em UTI neonatal: um estudo psicanalítico - Barreto, Cristiane Palmeira de Oliveira (2011)
The following dissertation has the purpose of studying the relation between mothering and mother s function in neonatal ICU. I intentionally propose to set a distance between the two concepts, being mothering the incumbency of the necessary caretaking for survival and mother s function, the practice of a symbolic function that relates the subject to its psychic constitution in its relation with the language field. In the present study, the inquiry consists in verifying whether the difficulty in practicing mothering, which occurs within the neonatal intensive care unit, may interfere with the conditions that support mother function or not, as a rule, practiced by the mother. The inquiry was conducted at a private hospital in São Paulo city, with mothers of both male and female babies, born preterm and admitted at the neonatal ICU and, subsequently, after discharge. The clinical extracts of the mother s saying during the interviews and presented in this paper are analyzed in the light of the Freud and Lacan psychoanalysis theory. And, regarding the investigation of the conditions for the performance of mother s function, I sought inspiration on the four theoretical axis formulated in the Clinical Indicators of Risk for the Child Development (IRDI). By listening to the mothers during and after the hospital admission reveals the presence of psychic impact caused by the preterm birth of a child and the admission in the neonatal ICU, as well as the difficulty in mothering the baby. Albeit, despite the psychic rapture, in the analysis of the symbolic function based on the four fundamental operations, deduced by me according to the IRDI -, it was possible to notice conditions for the mother s function to be performed